Synthesis, Spectral Characterization and DFT Calculations of New Co(II) Complexes Derived from Benzimidazoles - Zahra Safavi Rad; Mehdi Pordel; Abolghasem Davoodnia (Iranian Journal of Chemistry & Chemical Engineering, 2019)
The synthesis, characterization and quantum-chemical investigations of two new Co(II) complexesderived from fluorescent benzimidazoles have been reported. Two new fluorescentheterocyclic ligands were synthesized from the reduction of imidazo[4',5':3,4]benzo[1,2-c]isoxazole derivatives, and characterized by elemental analyses, IR, mass, and NMR spectra. Coordination of the bidentate ligands with Co(II) cation produced orange complexes. The structures of the complexes have been established by spectral and analytical data as well as Job’s method. The photophysical properties of the new ligands and Co(II) complexes were characterized by UV-Vis and fluorescence spectroscopies. An efficient charge transfer from the p-orbital of ligand to the Co(II) d-orbital could be proposed as the main reason for the color of the new complexes. To gain insight into geometry, spectral properties and the energy difference between the HOMO and LUMO frontier orbitals of the ligands and Co(II) complexes, the DFT calculations at the B3LYP/6-311++G(d,p) level were employed. The DFT-calculated spectral properties were in good agreement with the experimental values and confirmed the suitability of the optimized geometries for cobalt complexes.